Trois fois par mois ? dix fois par jour ? Montaigne et la réglementation du mariage dans « Sur des vers de Virgile » (Essais, III, 5) - Bjaï, Denis (AMU Press, 2011)
In his chapter “Upon some lines of Virgil” (Essays, III, 5), Montaigne relates the complaint of a poor Catalonian woman, to whom her husband fulfilled his conjugal duties at least ten times a day, and the arbitration the Queen of Aragon gave in her favour (?). This spicy story actually raises a tricky point of law, that Nicolas Bohier (Decisiones Aureæ, 1544), Antoine du Verdier (Les diverses leçons, 1577) and Guillaume Bouchet (Les Serées, 1584) had previously studied. After Montaigne, the case will be dealt with again in the works of Cholières and Brantôme.